A method to generate Harshad numbers - D’AMICO, Rosario (Journal of Mathematical Economics and Finance, 2019)
The purpose of this work is to create mathematical formula which generates Harshad numbers in base 10, which are positive integers (written in decimal form) divisible by the sum of their own digits.